CODE MIXING IN THE UTTERANCE OF TEACHER IN SEMARANG - Rini Esti Utami (Pusbindiklat - LIPI, 2011)
The utterance of teachers in Semarang is a representation of a language use of a bilingual society. The use of Indonesian at school is frequently influenced by the use of the teachers mother tongue, which is Javanese. Even though, they realize that the official language is Indonesian, with a certain purpose they mix code into Javanese. This descriptive qualitative study aims to see the form and the purpose of code mixing which is done by teachers in Semarang. Studying the form and the purpose of the code mixing is very important so that teachers will be wise and right in doing code mixing. Based on the study, the components of code mixing in the utterance of teachers in Semarang are covering phrases, idioms, and words of address. The words which are mixed are verbs, adjectives, adverbs, and prepositions. Meanwhile phrases which are mixed are noun phrase and verb phrase. The purpose of code mixing in the utterance of teachers in Semarang can be described as follows: to maintain the conversation, to show the familiarity, to respect the interlocutor, to emphasize something, and to fine or politeness.